Strategi Peningkatan PBB P2 terhadap Pendapatan Asli Daerah dengan Perspektif Wajib Pajak - Moch Anas Kurniawan; Dwi Cahyono; Achmad Syahfrudin (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study is to analyze the effect of taxation sanctions, taxpayer attitudes, taxpayer awareness and tax knowledge in increasing Jember Regency Regional Revenue (PAD). This research is a quantitative research with a descriptive approach. A sample of 100 respondents was obtained by cluster sampling technique. Data were obtained using a questionnaire and analyzed using two analytical methods, namely quantitative descriptive analysis and trend analysis. The results showed that the obstacle experienced by the Jember Regency government was because PBB P2 was a new tax so that the local government experienced difficulties in its management, inadequate facilities and infrastructure and large costs, and human resources that were not optimal in providing services. The Jember Regency Government carries out three stages of strategy, namely the strategic planning stage, strategy implementation and strategy evaluation. Conclusion, tax sanctions have a significant and positive effect on the increase in PAD, attitudes of taxpayers, awareness of taxpayers, knowledge of taxation has no significant effect but has a positive influence on the increase in PAD in Kabupaten Jember. Keywords: PBB P2, Strategy, Taxpayer Sanctions, Taxpayer Attitudes, Taxpayer Awareness and Tax Knowledge.